2006
DOI: 10.1007/s11892-006-0080-1
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and diabetic nephropathy

Abstract: Diabetic nephropathy has become the main cause of renal failure, but unfortunately the intimate mechanisms leading to the development and progression of renal injury are not yet fully known. Activated innate immunity and inflammation are relevant factors in the pathogenesis of diabetes. Moreover, different inflammatory molecules, including chemokines, adhesion molecules, and proinflammatory cytokines, may be critical factors in the development of microvascular diabetic complications, including nephropathy. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
120
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(127 citation statements)
references
References 74 publications
2
120
0
5
Order By: Relevance
“…21 Hemodialysis affects both oxidative stress and cellular inflammation. Various studies showed the increasing of the oxidative stress and the reduction of antioxidant defenses in patients with chronic renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…21 Hemodialysis affects both oxidative stress and cellular inflammation. Various studies showed the increasing of the oxidative stress and the reduction of antioxidant defenses in patients with chronic renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…DN was considered to be a nonimmune disease. Nevertheless, it has been shown recently that inflammation is crucial for the development of microvascular complications of DM, including nephr opathy (Mora and Navarro, 2006;Ortiz-Munoz et al, 2010).…”
Section: Pathophysiological Features Of Diabetic Nephro-pathymentioning
confidence: 99%
“…Moreover, it has been proved that IL-1beta, IL-6 and TNF-alpha are relevant for the developme nt of DN (Mocan et al, 2006;Mora and Navarro, 2006). IL-1beta and IL-6 increase vascular endothelial permeability and alter ECM dynamics at both the mesangial and podocyte levels, contributing to interstitial infi ltrates, glomerular basement membrane thickening, mesangial expansion, and tubula r atrophy (Pecoits-Filho et al, 2002;Dalla et al, 2005).…”
Section: Pathophysiological Features Of Diabetic Nephro-pathymentioning
confidence: 99%
“…Augmented inflammation is a hallmark of diabetes, 17,18 and this proinflammatory state plays a critical role in the development and progression of DN. 10,19,20 Elements of the diabetic milieu, such as hyperglycemia and advanced glycation endproducts are thought to play an important role in creating a proinflammatory environment in both peripheral circulation and renal tissues. 10,14,21,22 Moreover, the initial renal glomerular dysfunction is thought to result in macrophage infiltration due to increased expression of inflammatory adhesion and chemoattractant proteins.…”
mentioning
confidence: 99%